Endovascular recanalisation with drug coated balloon for chronic symptomatic middle cerebral artery total occlusion. (7th April 2018) - Zhang, Jun; Zhang, Xiao; Zhang, Jin-Ping; Han, Ju
Abstract : The optimal treatment for patients with chronic symptomatic middle cerebral artery (MCA) total occlusion is not well established. In addition to medical therapy, vessel recanalisation with stenting has shown much promise, especially for patients with recurrent ischemic symptoms. Nevertheless, the incidence of symptomatic in-stent restenosis (ISR) is high, and is associated with an unfavorable prognosis. Drug coated balloons (DCBs) have been proven to be effective in treating and preventing ISR. However, the feasibility of DCBs for de novo intracranial atherothrombotic stenosis has not been previously described, especially for total occlusion lesions. Here we reported a patient with chronic left MCA total occlusion successfully treated with DCBs, with a good outcome at the 1 year follow-up. More studies are warranted to further compare the efficacy of DCBs and stentings for intracranial revascularisation.